HUBUNGAN PROMOSI DENGAN KEPUTUSAN PEMBELIAN KAMAR TAMU DI HOTEL BUMIMINANG PADANG - Tiffany, Intan; Yuliana, Yuliana; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aimed to examine the relationship between promotion with purchasing decisions guestrooms at Hotel Bumiminang Padang. The population in this study is the guests who have stayed with the monthly average is 998 people. The number of samples in this study amounted to 91 people. The data collection techniques with indirect communication through a questionnaire ( questionnaire ) by using a Likert scale that has been tested for validity and reliability. The results showed that: (1) Promotions that are in good enough category with an average score of 50.29, (2) Purchase Decision Guestrooms in the category quite well with an average score of 52.37, (3) Results of Person Product Moment Correlation test showed that there is a relationship positive (strong) and significant correlation between promotion with purchasing decisions are assessed by guests who have stayed in Bumiminang Padang, with a correlation coefficient (r) of 0.509 (sig 0.000) with a strong category because it is in the range > 0.5-0.75.